2018
DOI: 10.1556/2006.7.2018.72
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between attention-deficit hyperactivity disorder symptoms and problem gambling: A mediation analysis of influential factors among 7,403 individuals from the UK

Abstract: Background and aimsOur goal was to examine the association between attention-deficit hyperactivity disorder (ADHD) symptoms and gambling problems, and to identify potential mediating factors of this association.MethodsThis study used cross-sectional, community-based data from 7,403 people aged ≥16 years who participated in the Adult Psychiatric Morbidity Survey 2007. ADHD symptoms were assessed using the Adult ADHD Self-Report Scale (ASRS) Screener. Problem gambling was assessed using a questionnaire based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 78 publications
2
11
2
Order By: Relevance
“…Specifically, young adult smokers present twice the possibility to score positive on an ADHD screening questionnaire (OR = 1.82, IC95% = 1.00-3.30) than non-smoking young adults. Compared to other studies [52][53][54], no similar results have been found in BDZ users, gambling and alcohol use. It is important to underline that we have used a screening questionnaire for ADHD, and not a diagnostic one.…”
Section: Discussioncontrasting
confidence: 85%
“…Specifically, young adult smokers present twice the possibility to score positive on an ADHD screening questionnaire (OR = 1.82, IC95% = 1.00-3.30) than non-smoking young adults. Compared to other studies [52][53][54], no similar results have been found in BDZ users, gambling and alcohol use. It is important to underline that we have used a screening questionnaire for ADHD, and not a diagnostic one.…”
Section: Discussioncontrasting
confidence: 85%
“…For example, the literature has highlighted the robust link between behavioral addiction and neurodevelopmental disorders characterized by inattention and hyperactivity-impulsivity, such as the presence of attention-deficit hyperactivity disorder (ADHD) (Brandt & Fischer, 2019). Various hypotheses have been suggested to explain the mechanisms linking ADHD (particularly when it persists in adulthood) with GD (Jacob, Haro, & Koyanagi, 2018), high impulsivity levels being one of the core features (Abouzari, Oberg, Gruber, & Tata, 2015). It has also been postulated that children with ADHD usually report lower intelligence quotient (IQ) than control subjects (Biederman, Fried, Petty, Mahoney, & Faraone, 2012), and the combination of high impulsivity levels with lower IQ could lead to a higher risk of GD (Rai et al, 2014).…”
Section: Relevance Of Impulsivity As a Core Mechanism In The Gd Areamentioning
confidence: 99%
“…66,67 Harms associated with people who experience gambling disorder include financial problems, problems with interpersonal relationships, 68,69 and associations with other psychiatric disorders. 70,71 Youth may be a particularly susceptible population for gambling problem harms. Therefore, it is important to understand the use of age restrictions in preventing or minimising these harms.…”
Section: Overview Of Age Restrictions and Gamblingmentioning
confidence: 99%